2014
DOI: 10.1177/0022022114557487
|View full text |Cite
|
Sign up to set email alerts
|

What Kinds of Value Motives Guide People in Their Moral Attitudes? The Role of Personal and Prescriptive Values at the Culture Level and Individual Level

Abstract: Opinions about moralized issues are arguably one of the most difficult issues in interpersonal dialogues given that they can result in intolerance and prejudicial behavior toward those with divergent moral beliefs. Recent research has shown that moral attitudes vary not only depending on the individual's characteristics but also as a function of culture. Individuals from individualistic-oriented cultures exhibit more lenient judgments toward moralized issues than those from collectivistic-oriented cultures. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…Values have been a crucial concept ever since the early beginnings of psychological research (see Vernon & Allport, 1931). They have been widely used to explain people’s attitudes (e.g., Dobewall & Rudnev, 2014; Vauclair, Fischer, et al, 2015), emotions (Roccas & McCauley, 2004; Sortheix & Lönnqvist, 2014), and behaviors (e.g., Fischer & Boer, 2015; Verplanken & Holland, 2002). Human values are commonly defined as relatively stable , desirable, transsituational motivational goals, which vary in their relative importance and serve as individuals’ guiding principles in life (Schwartz, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Values have been a crucial concept ever since the early beginnings of psychological research (see Vernon & Allport, 1931). They have been widely used to explain people’s attitudes (e.g., Dobewall & Rudnev, 2014; Vauclair, Fischer, et al, 2015), emotions (Roccas & McCauley, 2004; Sortheix & Lönnqvist, 2014), and behaviors (e.g., Fischer & Boer, 2015; Verplanken & Holland, 2002). Human values are commonly defined as relatively stable , desirable, transsituational motivational goals, which vary in their relative importance and serve as individuals’ guiding principles in life (Schwartz, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Using SVS measures, used data on teachers (66 countries) and students (55 countries) to validate the structure of Schwartz values at the level of culture and to propose a new value type: self-fulfilled connectedness. Vauclair et al (2015) studied four collectivist countries (Brazil, Japan, Philippines, and Turkey) and four individualistic countries (Finland, Germany, New Zealand, and the U.K.). The study found that moral judgments were more stringent in "conservation cultures" than in "openness to change cultures" (Vauclair et al 2015).…”
Section: Valuesmentioning
confidence: 99%
“…Vauclair et al (2015) studied four collectivist countries (Brazil, Japan, Philippines, and Turkey) and four individualistic countries (Finland, Germany, New Zealand, and the U.K.). The study found that moral judgments were more stringent in "conservation cultures" than in "openness to change cultures" (Vauclair et al 2015). However, this relationship only appeared from culture to individual: a culturally prescribed value correlated with individual moral attitude; but openness to change or conservation at the individual level did not corelate with individual moral attitudes.…”
Section: Valuesmentioning
confidence: 99%
“…Despite a still unfounded relationship between the personal values of accountants and non-accountants and their personal tax culture, personal values were already studied by many authors in the past. Feldman (2015), Schwartz (1992), Sezer et al (2015), Litina and Palivos (2016), Gino (2015), Alleyne et al (2013), Fischer and Poortinga (2012), Fischer, et al (2010), and Vauclair et al (2015) studied factors influencing the shaping of individuals and consequently their personal culture. They established that personal values were supposed to have the key role in motivating for ethical decision and behaviour of individuals.…”
Section: Personal Tax Culture: Literature Reviewmentioning
confidence: 99%